(untitled) (Asia Pacific Journal of Social and Behavioral Sciences, 2013)
This paper described and analyzed the population distribution of Bukidnon. A fractal analysis was used by computing the fractal dimensions of the population distribution of the province. Data are based on the population of 20 municipalities and two (2) cities in 16 years, from 1995 to 2010. The results showed that there is a slight decrease of fractal dimensions which implies that there is an approximately equal population in the municipalities over a period. Various conditions account for the decrease of variability in the population distribution. It may be attributed to their economic situations and cultural practices.